Lung Cancer Prevalence in Hill Region of Nepal - Bhatta, Pramod; Shrestha, Bhakta Man (Journal of Advanced Academic Research, 2018)
Nepal being one of the low and middle income countries where disease pattern shifted from communicable to non communicable diseases such as heart and cancer diseases since past. Primary focus of the study was to explore the prevalence of lung cancer in Hill region of Nepal. The study survey was conducted in BP Koirala Memorial Cancer Hospital, Bharatpur Chitwan. The study applied quantitative research design. The data was collected from the records of 800 cancer diagnosed patients of the hospital. The record was collected and analyzed from 160 randomly selected cancer cases from year 2009 to 2013. The study was non experimental, descriptive, exploratory and cross-sectional research design. Findings suggested that lung cancer cases were high 32.9% in Hill region. Smoking habit was also found in 56.1% patients, the findings suggested that the reason of high lung cancer might be attributable to high smoking prevalence. High lung cancer prevalence found in Hill region of Nepal which signifies the need of further investigation on lung cancer and related risks in these areas.